Fijian students’ perceptions drawn on Indian popular culture: exploring cultural hybridity and the twice-removed-from-reality image of India - Sakul Kundra; Nakul Kundra; Unaisi Nabobo-Baba; Nii-K Plange; Amit Sarwal; Bhawna; Romina Singh; Regina Naidu (Cogent Arts & Humanities)
Fiji, a multilingual and multicultural nation, is often termed ‘Little India’ where the Fijians of Indian descent (Indo-Fijians) have developed a new identity through cultural assimilation as well as accommodation. At present, Indo-Fijians are consumers of the ‘twice-removed-from-reality’ (Plato) image of India, which is constructed through Bollywood movies, Hindi television serials, music, print media, and other common forms of popular culture. Their lifestyle with some distinct Indian cultural traits and their interests in Indian popular culture have unwittingly influenced their fellow indigenous Fijian youths (iTaukei) in several ways. It is observed that many iTaukei have developed a keen interest in Bollywood movies and Indian TV serials. They have formed their perceptions about Indian life and society without having been to India. This research attempts to find out Fijian students’ perceptions of Indian life and culture; it is based on a qualitative survey of 110 undergraduate students (75% of iTaukei and 25% of non-iTaukei [predominantly the Fijians of Indian descent]), followed by interviews based on closed and open-ended questions to understand their cultural hybridity and the rationale behind their perceptions.